Hero of the Pacific : the life of Marine legend John Basilone - Brady, James, 1928-2009 (John Wiley, 2010)
"Can a single night define a man's life? From the summer of 1943 to early 1945, John Basilone was one of the most famous and admired people in America. As the first enlisted man to be awarded the Medal of Honor in World War II, for extraordinary bravery under fire at Guadalcanal, he toured the nation with movie stars, shared podiums with mayors and governors, shook the hands of thousands of citizens, and was even rumored to have made a romantic connection with a beautiful young actress. Why would a man who had proven his courage beyond any doubt, who had gone above and beyond the call of duty, and was reaping the rewards of his sacrifice beg his commanding officers to break with tradition and send a Medal of Honor winner back into combat? Legendary columnist James Brady explores this and many other puzzling questions in this thrilling and surprising biography. Hero of the Pacific tells the dramatic and compelling life story of a small-town boy who became one of World War II's greatest and best-known heroes, only to be forgotten after his death during another famous and hellish battle on Iwo Jima. You may never have heard of John Basilone, but once you read this powerful tale, you'll never forget him"--Publisher's description.